Chemical Analysis and Electrochemical Monitoring of Extremely Low-Concentration Corrosive Impurity MgOHCl in Molten MgCl2–KCl–NaCl - Gong, Qing; Ding, Wenjin; Chai, Yan; Bonk, Alexander; Steinbrecher, Julian; Bauer, Thomas (Frontiers in Energy Research, 2022)
MgCl2–KCl–NaCl is a promising thermal energy storage (TES) material and heat transfer fluid (HTF) with high operating temperatures of >700°C for next-generation concentrating solar power (CSP) plants. One major challenge for future implementation of the molten chloride TES/HTF technology arises from the presence of some corrosive impurities, especially MgOHCl, a hydrolysis product of hydrated MgCl2. Even extremely low-concentration MgOHCl (tens of ppm O in weight) can cause unneglectable corrosion of commercial Fe–Cr–Ni alloys, which limits their service time as the structural materials in the molten chloride TES/HTF system. Thus, the chemical analysis and monitoring techniques of MgOHCl at the tens of ppm O level are vital for corrosion control. In this work, a chemical analysis technique based on direct titration and a high-precision automatic titrator was developed for an exact measurement of MgOHCl at the tens of ppm O level. It shows a standard deviation below 5 ppm O and an average error below 7 ppm O when the concentration of MgOHCl is 36 ppm O. Moreover, compared to other methods available in some literature reports, it can exclude the influence of co-existing MgO on the MgOHCl concentration measurement. This chemical analysis technique was used to calibrate the previously developed electrochemical method based on cyclic voltammetry (CV) to achieve reliable in situ monitoring of MgOHCl in the MgCl2–KCl–NaCl molten salt at a concentration as low as the tens of ppm O level. The in situ monitoring technique shows a monitoring limitation of <39 ppm O. The two techniques for MgOHCl measurement developed in this work could be used to develop an in situ corrosion control system to ensure the long service time of the molten chloride TES/HTF system in next-generation CSP plants.